Oferta académica de la Carrera de Enfermería de la Universidad Estatal de Bolívar relacionada con la Empleabilidad de los y las graduadas en la zona 3. año 2018-2020 - Bonilla Bonilla, Carmen Elizabeth (2022)
Each Institute of higher education has particular characteristics that differentiate it from the rest of its other equals that offer the same university degree. The academic offer represents an important element when it comes to presenting the particular advantages of the graduate's professional profile that will favor their future employability. The objective of this research was "To determine the relationship between the academic offer of the Nursing Career of the Bolívar State University and the employability of graduates who are working in Zone 3 during the 2018-2020 period." For this, a quantitative research methodology was implemented to determine the trends in the academic offer and employability in Zone 3 at a correlational level to infer the current relationship between both variables. The population was selected applying inclusion criteria, leaving the sample made up of 27 graduates between 2018 and 2020 who agreed to provide information, using the closed questionnaire as an instrument and the survey using Google Forms as a technique to comply with the standards of biosecurity and social distancing. The results after the analysis indicated that graduates of the Bolívar State University in the Nursing Career work according to the academic offer and what is required in the labor market of zone 3, where 100% work in Public Health Institutions , complying with the requirements of employers. Conclusion: the academic offer of the Nursing Career is related to the employability of zone 3. Keywords: academic offer, employability, graduates